2022
DOI: 10.15244/pjoes/150642
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal-Spatial Evolution and Driving Mechanism of Rural Green Development in China

Abstract: Green development is the inherent requirement and important support of comprehensive rural revitalization in China. This study constructs a rural green development index system drawing on the framework of "green growth-green wealth-green welfare" and elaborates the temporal-spatial evolution and driving mechanism of rural green development in 30 provinces in China based on the entropy method, spatial autocorrelation analysis and Geodetector. The results indicate that the rural green development index (RGDI) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This data was obtained from the local land administration and we converted it to raster data with a resolution of 10 m for use. Referring to the classification principles and methods in related literature (A. Wang et al, 2022; J. Wang et al, 2023) and combining with the land use cover characteristics of dryland areas and the main purpose of this study, it was classified into three primary classifications of production space, living space and ecological space and seven secondary classifications (Table S1). (2) Spatial data for geographical elements for administrative boundaries at all scales, traffic network, and river systems in the study area were extracted from the National Geomatics Center of China (http://www.ngcc.cn/ngcc/).…”
Section: Methodsmentioning
confidence: 99%
“…This data was obtained from the local land administration and we converted it to raster data with a resolution of 10 m for use. Referring to the classification principles and methods in related literature (A. Wang et al, 2022; J. Wang et al, 2023) and combining with the land use cover characteristics of dryland areas and the main purpose of this study, it was classified into three primary classifications of production space, living space and ecological space and seven secondary classifications (Table S1). (2) Spatial data for geographical elements for administrative boundaries at all scales, traffic network, and river systems in the study area were extracted from the National Geomatics Center of China (http://www.ngcc.cn/ngcc/).…”
Section: Methodsmentioning
confidence: 99%
“…Other scholars have evaluated the development level of the green competitiveness of municipalities based on four dimensions [12], namely economic green development, social green development, resource green development, and environmental green development, or three dimensions [13], namely green economy, green investment, green utilization, and green security. In addition, Wang et al (2022) constructed a comprehensive evaluation index system for green competitiveness in rural China based on the "green growth-green wealth-green welfare" framework [14]. (3) On the spatio-temporal patterns of green competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies show that China's regional green competitiveness continues to improve, with the green competitiveness of the eastern region being much higher than that of the other regions, and the regional differences are characterized first by an increase and then a decrease; the coupling coordination degree of China's regional green competitiveness system exhibits significant spatial dependence, forming a high-coupling coordination degree agglomeration with Shanghai as the center spreading to the south and a low-coupling coordination degree agglomeration with Qinghai as the center spreading to the east [11]. Wang et al (2022) analyzed the spatial and temporal characteristics and drivers of China's rural green competitiveness through spatial autocorrelation (SA) analysis and GeoDetector and found that China's rural green development presents a spatial differentiation feature that is high in the eastern region and low in the central and western regions [14]. Ma et al (2023) analyzed regional differences in China's green competitiveness through methods such as coefficient of variation analysis and found that the coefficient of variation in green competitiveness of China's 30 provinces and the eastern, central, and western regions show an inverted U-shape trend of first increasing and then decreasing [19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we aim to develop a comprehensive evaluation system for urban vulnerability to serve as a reference for assessing the overall quality of urban development and promoting sustainable development for both people and the environment. In recent years, with the gradual popularization of the "three pillars" concept in the international community, academics have increasingly focused on the study of territorial space from a production-living-ecological perspective [23,24]. The integrated spatial layout of production-livingecological space plays a crucial role in harmonizing the relationship between people and the land and provides a methodology for improving the quality of urban development and reducing urban vulnerability.…”
Section: Introductionmentioning
confidence: 99%